Socioeconomic status, linguistic skills and language background differentially relate to preschoolers' emotional and behavioural profile - Paola Bonifacci; Viola Ravaldini; Martina Cangelosi; Valentina Tobia (BMC, 2024)
Abstract Background Proximal and distal factors interact to shape children's development and well-being. The present study aimed to examine socioeconomic status (SES), linguistic skills, and language background as concurrent predictors of socio-emotional and behavioural outcomes in heritage bilingual and monolingual children attending preschool. Methods Parents of 1810 children (mean age = 63.42 months ± 7.36), attending preschool in Italy, completed the Four Factor Index of SES and the Strengths and Difficulties Questionnaire (SDQ). Teachers (n = 99) completed a questionnaire on children's linguistic skills and emotional and behavioural profiles. A subsample of 995 children was administered an expressive vocabulary task in Italian. Results Regression analyses showed that linguistic skills were the only concurrent predictor of conduct problems, as well as the dominant predictor of hyperactivity/impulsivity, peer problems, and better prosocial behaviour. SES was negatively related to ADHD traits, peer problems, and prosocial behaviour. Finally, heritage bilingualism background was associated, although not as a primary predictor, with increased emotional problems, peer relationship problems, and lower teacher-rated emotional and behavioural skills. However, it was the main factor positively associated with prosocial behaviour. Conclusions The implications of these findings for research in this area and for educational policy are discussed, highlighting the need for a multidimensional perspective that includes linguistic skills and SES in the assessment of children's emotional and behavioural outcomes.